Hypertensive Patients’ Perceptions of Their Disease: A Phenomenological Study - Dinar Herdhiyanti Siwi; Burhannudin Ichsan (LPPM STIKes Muhammadiyah Ciamis, 2026)
Hypertension is a non-communicable disease with high prevalence and a substantial risk of serious complications if not properly managed. Patients’ perceptions of hypertension play a crucial role in shaping health-related behaviors, particularly medication adherence and the adoption of healthy lifestyles. This study aims to explore and analyze patients’ perceptions of hypertension, the factors influencing these perceptions, and their implications for disease management and treatment adherence. This study employed a qualitative phenomenological design. Data were collected through semi-structured in-depth interviews with 17 patients diagnosed with hypertension who attended routine follow-up visits at Nogosari Primary Health Care Center, Boyolali, Central Java, Indonesia. Participants were selected until data saturation was achieved. Data were analyzed using thematic analysis. The findings showed that all patients perceived hypertension as a dangerous disease, mainly due to the risk of complications such as stroke and heart disease. However, patients’ levels of understanding regarding the definition, disease mechanisms, and complications of hypertension varied. Hypertension management, as perceived by patients, included dietary regulation, physical activity, stress management, and regular medication use, although inconsistencies in implementation were reported. Better perceptions of hypertension tended to encourage improved medication adherence and healthier lifestyle behaviors. This study highlights the importance of continuous health education to enhance patients’ understanding and management of hypertension.